hLMSC Secretome Affects Macrophage Activity Differentially Depending on Lung-Mimetic Environments - Bryan Falcones; Zackarias Söderlund; Arturo Ibáñez-Fonseca; Isaac Almendros; Jordi Otero; Ramon Farré; Sara Rolandsson Enes; Linda Elowsson Rendin; Gunilla Westergren-Thorsson (Cells, 2022)
Mesenchymal stromal cell (MSC)-based therapies for inflammatory diseases rely mainly on the paracrine ability to modulate the activity of macrophages. Despite recent advances, there is scarce information regarding changes of the secretome content attributed to physiomimetic cultures and, especially, how secretome content influence on macrophage activity for therapy. hLMSCs from human donors were cultured on devices developed in house that enabled lung-mimetic strain. hLMSC secretome was analyzed for typical cytokines, chemokines and growth factors. RNA was analyzed for the gene expression of CTGF and CYR61. Human monocytes were differentiated to macrophages and assessed for their phagocytic capacity and for M1/M2 subtypes by the analysis of typical cell surface markers in the presence of hLMSC secretome. CTGF and CYR61 displayed a marked reduction when cultured in lung-derived hydrogels (L-Hydrogels). The secretome showed that lung-derived scaffolds had a distinct secretion while there was a large overlap between L-Hydrogel and the conventionally (2D) cultured samples. Additionally, secretome from L-Scaffold showed an HGF increase, while IL-6 and TNF-α decreased in lung-mimetic environments. Similarly, phagocytosis decreased in a lung-mimetic environment. L-Scaffold showed a decrease of M1 population while stretch upregulated M2b subpopulations. In summary, mechanical features of the lung ECM and stretch orchestrate anti-inflammatory and immunosuppressive outcomes of hLMSCs.